Synthesis of Phosphorus Doped Graphenes via the Yucel's Method as the Positive Electrode of a Vanadium Redox Flow Battery - Gursu, Hurmus; Gencten, Metin; Sahin, Yucel (ELECTROCHEMICAL SOC INC, 2021)
Improving electrode performances in the high-current cycles is essential to increase the global competitiveness of vanadium redox flow battery (VRFB), a widespread application potential for large-scale energy storage systems. Modifying carbon electrode surfaces with graphene-based materials and even doping of graphene with heteroatoms is a reasonably critical strategy to enhance the reaction activity and reversibility of vanadium redox couples. In this study, phosphorus-doped graphene-based electrodes were produced via Yucel's method in phosphoric acid solution, and their use as positive electrodes for VRFB was investigated. Various electrochemical, spectroscopic, and morphologic characterization methods were used to analyze the electrodes. The effects of P-doped graphene-based materials as the positive electrode of VRFB were investigated via electrochemical methods such as cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and cyclic charge-discharge. The VRFB with phosphorous doped graphene-based electrodes prepared in the potential range between -1.0 and +2.1 V (P-GPGE1) exhibited higher discharge capacity as 1.11 Ah l(-1), and energy efficiency as 73.1% at the charge and discharge current densities of 8 and 1.6 mA.cm(-2), respectively. This paper reveals a promising way to produce phosphorous doped graphene-based electrodes for the next-generation VRFB, a high-power, stable, and efficient operation.
Keywords: Phosphorus doped graphene; Yucel' s method; cyclic voltammetry; vanadium redox flow battery; positive electrode; cyclic charge-discharge; IN-SITU RAMAN; CHEMICAL-VAPOR-DEPOSITION; CARBON FELT ELECTRODES; ELECTROCHEMICAL EXFOLIATION; ELECTROCATALYTIC ACTIVITY; RENEWABLE ENERGY; OXIDE; GRAPHITE; NITROGEN; EFFICIENT; Electrochemistry; Materials Science